A New Record for Loose Smut in the Libyan Jamahiriya - ABUGHNIA, ABDULNABI (The Libyan Journal of Agriculture, 2023)
Imperata cylindrica Beauv. is a weed competing with other crops. It is called “Sbatt’ in the Libyan Jamaheria and was found in Tajoura, Gharabouli, Jofra and Ghat. In spring of 1979, loose smut was observed for the first time on Imperata cylindrica Beauv. in Gharabouli agricultural project near a barley field and also in Tajoura. The fungus was identified as Ustilago imperata and considered as a new record in the Libyan Jamaheria (1, 2). DISCRIPTION OF THE FUNGUS Sori entirely distroying the infourescence, protected by greyish membrane of host tissue which later flakes away revealing a pulverulnt, black spore masses. No sterile cells observed. Spores spherical with granuler contents, brown to natal brown, 11-1 Ip in diameter with a mean average of 15 ,u. Epispore smooth with thick wall, germination by septate promycelium with lateral sporodia.